2016
DOI: 10.1097/ccm.0000000000001382
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome Following Tracheostomy in Critical Care

Abstract: Considering comparative data, there was no significant difference in the prevalence of tracheal stenosis or major bleeding between percutaneous and surgical tracheostomy. In relation to wound infection, we have found a reduction associated with the original Ciaglia technique when compared with that with the surgical tracheostomy. Considering all published data reporting long-term outcomes pooled proportion meta-analysis indicates a trend toward a higher rate of tracheal stenosis and an increased risk of major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 56 publications
3
19
0
2
Order By: Relevance
“…However, this data is consistent with previous studies that showed the incidence of tracheal stenosis after tracheostomy is low (1%-6%). 1 The risk factors associated with this group are a continued source of debate. This study was not designed to answer these questions; however, when comparing the 1% of patients who were identified as developing tracheal stenosis after tracheostomy to other tracheostomy patients, there were no differences in age, gender, pneumonia, sepsis, or length of stay during their index admissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this data is consistent with previous studies that showed the incidence of tracheal stenosis after tracheostomy is low (1%-6%). 1 The risk factors associated with this group are a continued source of debate. This study was not designed to answer these questions; however, when comparing the 1% of patients who were identified as developing tracheal stenosis after tracheostomy to other tracheostomy patients, there were no differences in age, gender, pneumonia, sepsis, or length of stay during their index admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheal stenosis due to tracheostomies is an uncommon but significant condition that can occur among tracheostomy patients. 1 It can be associated with adverse outcomes, including prohibiting the ability to decannulate a patient once the primary indication for the tracheostomy has resolved. Currently, the generalizability of research examining the demographics and the incidence of tracheal stenosis due to tracheostomy are limited because studies are primarily single institutional experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Late complications included 5 (0.16%) cases of tracheal stenosis requiring intervention without associated deaths. 21 Tracheal stenosis as a late complication also appeared more often in patients who had ST. 22 There is no significant difference in hemorrhage incidence and mortality when PDT and ST were compared. However, lower risk of infection and shorter duration of the procedure favors the percutaneous technique.…”
Section: Discussionmentioning
confidence: 93%
“…Тем не менее большинство авторов считают трахеостомию ранней, если она выполняется на 3-10-е сутки, а поздней -на 10-15-е сутки проведения ИВЛ [36]. Результаты многоцентровых исследований, проведенные метаанализы и данные Кохрейновской библиотеки свидетельствуют о том, что в популяции общереанимационных пациентов трахеостомию следует выполнять спустя 7-10 сут после проведения ИВЛ, а у нейрореанимационных пациентов -на 3-7-е сутки [37,38]. При «ранней» трахеостомии достоверно снижается потребность в седации, уменьшается время проведения ИВЛ и пребывания пациента в отделении реанимации [39].…”
Section: доступ к дыхательным путям неинвазивная и инвазивная ивлunclassified